Who does not need a statin: too late in end-stage renal disease or heart failure?. Issue 9 (14th August 2008) - Laufs, U; Custodis, F; Böhm, M
Abstract : Current guidelines from large randomised trials recommend that all patients with diabetes type 2 or coronary artery disease after myocardial infarction should be treated with statin drugs. However, the recent 4D and CORONA trials show no improvement in mortality in elderly patients with ischaemic heart failure and patients with diabetes and end-stage renal disease receiving haemodialysis with the onset of statin treatment. The survival benefit from statin treatment appears to stem primarily from the prevention of progression of coronary artery disease. In clinical conditions where coronary artery disease does not significantly contribute to the cause of death statins seem to be less effective. In patients at risk for organ damage, statin treatment, therefore, has to be started early in the course of the disease. The effect of statin withdrawal in ischaemic heart failure or in patients with advanced renal disease is not known. On the basis of the available evidence, current statin treatment should not be stopped in these patients.